2003
DOI: 10.1348/000712603321661903
|View full text |Cite
|
Sign up to set email alerts
|

The effects of morphology on the processing of compound words: Evidence from naming, lexical decisions and eye fixations

Abstract: The use of lexemes during the recognition of spatially unified familiar English compounds was examined in naming, lexical decision and sentence-reading tasks by manipulating beginning and ending lexeme frequencies while controlling overall compound frequencies. All tasks revealed robust ending lexeme frequency effects, with compound processing being more effective when the ending lexeme was a high-frequency word. Beginning lexeme frequency effects were more elusive and dependent on task demands. Eye movements,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
151
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(178 citation statements)
references
References 20 publications
(36 reference statements)
23
151
4
Order By: Relevance
“…Measures were taken to ensure that the variation in word frequency would primarily reflect the degree of processing difficulty on the lexical level. One such measure was to control for morphological complexity according to CELEX (see Andrews, Miller, & Rayner, 2004;Juhasz, Starr, Inhoff, & Placke, 2003;Pollatsek, Hyönä, & Bertram, 2000 for evidence of effects of morpheme processing on reading time measures). A further step was to exclude words with extreme values in overall orthographic regularity, as indicated by mean positional bigram frequencies.…”
Section: Methodsmentioning
confidence: 99%
“…Measures were taken to ensure that the variation in word frequency would primarily reflect the degree of processing difficulty on the lexical level. One such measure was to control for morphological complexity according to CELEX (see Andrews, Miller, & Rayner, 2004;Juhasz, Starr, Inhoff, & Placke, 2003;Pollatsek, Hyönä, & Bertram, 2000 for evidence of effects of morpheme processing on reading time measures). A further step was to exclude words with extreme values in overall orthographic regularity, as indicated by mean positional bigram frequencies.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, a psycholinguistic reason for changing the frequency of digits would be that they are probably considered as a class of signs in the human processor and therefore should be annotated with their class frequency. Compounds with hyphens on the other hand should not be annotated with the frequency for the whole compound, as there is evidence in the literature on compound reading that the reading durations of compounds are primarily dependent on the frequency of the first part of the compound (Juhasz, Starr, Inhoff, & Placke, 2003).…”
Section: Issues Specific To Corpus Datamentioning
confidence: 99%
“…These facilitatory morphological effects are in accord with previous reports of visual lexical decision experiments with Dutch and English compounds (cf., e.g., Andrews, 1986;De Jong et al, 2000;De Jong et al, 2002;Juhasz et al, 2003).…”
Section: Insert Table 2 Approximately Herementioning
confidence: 99%
“…Whatever the disadvantages of our methodology may be, the pattern of results that we have obtained and reported either in the body of the paper or in Appendix 1, dovetails perfectly with many of the results obtained in the literature for sentential reading, such as visuo-oculomotor effects (cf., e.g., O'Regan et al, 1994;Rayner, 1998;Vitu, McConkie, Kerr & O'Regan, 2001), effects of compound length and frequency, as well as of constituent frequencies (cf., e.g., Andrews et al, 2004;Duñabeitia, Perea & Carreiras, 2007;Hyönä & Pollatsek, 1998;Hyönä et al, 2004;Juhasz et al, 2003;Taft & Forster, 1976), and effects of orthographic n-grams (reported in Appendix 1, cf., e.g., Lima & Inhoff, 1985). Furthermore, in a recent sentential reading study (Kuperman, Bertram & Baayen, 2008), in which Finnish compounds were embedded in context, a highly similar pattern of results was observed, including early effects of compound frequency, left constituent frequency and family size, later and weaker effects of right constituent frequency and family size, interactions between morphological predictors, as well as longitudinal experimental effects.…”
mentioning
confidence: 99%